A population‐based analyses of the evolving management of cN1M0 prostate cancer in the PSMA‐PET era - Jennifer Ward; Kevin Armstrong; Therese Min‐Jung Kang; Jodie Tham; Yuan‐Hong Lin; Marcus Cheng; Jeremy Grummet; Nathan Lawrentschuk; Marlon Perera; Shomik Sengupta; David Chang; Michael Ng; et al. (BJUI Compass)
Abstract Objectives To evaluate the patterns of management of clinical node‐positive non‐metastatic prostate cancer (cN1M0PC) at a population‐based level over time, and to identify factors associated with the different management approaches. Patients and methods The study included men diagnosed with cN1M0PC in Prostate Cancer Outcome Registry Victoria (PCOR‐Vic) in Australia between 2008 and 2022. The primary outcome was the use of local therapy (radical prostatectomy or prostate+/− pelvic radiation therapy) within the first 12 months of diagnosis. Multivariable logistic regressions were used to evaluate factors associated with local therapy use among all men and the likelihood of having a radical prostatectomy among men who had local therapy. Results Of the 819 men included in this study, 52% had PSMA‐PET staging, and this increased over time to 74% in 2018–2022. There were 530 (65%) who had local therapy (169 radical prostatectomy, and 361 radiation therapy), 259 (32%) had systemic therapy alone, and 30 (4%) did not have any treatment. There was an increase in the proportion of men who had local therapy over time, from 52% in 2008–2012 to 72% in 2018–2022. In multivariable analyses, increased age, higher PSA and residency in regional/remote areas were independently associated with lower likelihood of local therapy use, while PSMA‐PET staging and more recent year of diagnosis were associated with higher likelihood of local therapy use. Of the 530 men who had local therapy, increased age, higher PSA, higher ISUP grade group and higher clinical T categories were associated with a lower likelihood of having radical prostatectomy while men diagnosed in private institutions and from higher socioeconomic quintiles were more likely to have radical prostatectomy. Conclusion This is the largest contemporaneous population‐based study on the management of cN1M0PC in the PSMA‐PET era. There is an increasing use of local therapy for cN1M0PC over time, with large variations in practice.